2021
DOI: 10.2147/oarrr.s282612
|View full text |Cite
|
Sign up to set email alerts
|

The Updated Role of Ultrasound in Assessing Dermatological Manifestations in Systemic Sclerosis

Abstract: Systemic sclerosis (SSc), an autoimmune connective tissue disease, characterized by skin fibrosis, increased dermal thickness and microvascular involvement. Fibroblasts and myofibroblasts deposit excessive amounts of collagenous and non-collagenous extracellular matrix components in the skin. This leads to microvascular abnormalities and Raynaud’s phenomenon, with painful digital ulcers (DU) at the fingertips adding to patient discomfort. The skin involvement and severity in SSc was evaluated by the Modified R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…As the disease progresses, sclerodactyly becomes a leading cause of hand disability, increasing the risk for small joint contractures and digital ulcers. While the use of US to assess skin thickness is not widely adopted into clinical practice, there are numerous studies suggesting a positive correlation between US-measured skin thickness and histological skin thickness [30,31].…”
Section: Skin Thickeningmentioning
confidence: 99%
“…As the disease progresses, sclerodactyly becomes a leading cause of hand disability, increasing the risk for small joint contractures and digital ulcers. While the use of US to assess skin thickness is not widely adopted into clinical practice, there are numerous studies suggesting a positive correlation between US-measured skin thickness and histological skin thickness [30,31].…”
Section: Skin Thickeningmentioning
confidence: 99%
“…Meanwhile, Zhang et al ( 14 ) found that the skin elasticity and the surface wave velocity of patients with SSc positively correlate with the modified Rodnan skin score, while there is no correlation between skin viscosity and the modified Rodnan skin score. The author of this article previously conducted an exploratory study of ultrasound manifestations in scleroderma (all lesions were compared with peripheral or contralateral normal skin) and summarized it as follows ( 23 , 24 ): in the oedematous phase, there were dermal thickening and a reduction in echogenicity of the skin, without apparent changes in the subcutaneous layer, probably because of inflammatory exudation from the lesion, as well as increased fluid in the skin, resulting in swelling and thickening. Meanwhile, the skin elasticity was mildly elevated, and the blood flow signal was enhanced.…”
Section: Ultrasonography In Autoimmune Skin Diseasesmentioning
confidence: 99%
“…Systemic sclerosis (SSc) is a connective tissue disease characterized by immune and endothelial dysfunction, inflammation and fibrosis [1][2][3][4][5][6][7][8]. The main cause of death in SSc patients is the effect that collagen overproduction has on the internal organs, such as the pulmonary system [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%